Hydrothermal Synthesis and Crystal Structure of New (4,4)-Connected Ni(II) Coordination Polymer Based on 3,5-di(4'-Carboxylphenyl)benzene and 1,4-bis(Imidazol-1-yl)benzene - Zhang, Shuxin (Asian Journal of Chemistry, 2014)
A new coordination polymers [Ni2(L)(HL)2(bimb)2.5(H2O)]n (1) (H2L=3,5-di(4'-carboxylphenyl)benzene and bib=1,4-bis(imidazol-1-yl)benzene), has been prepared by hydrothermal synthesis. Complex [Ni2(L)(HL)2(bimb)2.5(H2O)]n (1), triclinic, space group P-1 with a = 10.472 (5) Å, b = 13.610 (5) Å, c = 27.738 (5) Å, b = 98.648 (5)° V = 3755 (2) Å3, Z = 2, Mr = 1609.92, Dc = 1.424 g/cm3, F (000) = 1666 and μ = 0.58 mm-1. The final refinement gave R = 0.0519 and wR = 0.1236 for 5110 reflections with I > 2s (I). X-ray diffraction analysis reveals that complex 1 shows a three-dimensional structure with a rare (4,4)-connected tcj/hc topological net.